Living buddhas: the self-mummified monks of Yamagata, Japan - Jeremiah, Ken (McFarland, 2010)
"Northern Japan is home to the tradition of self-mummifying Buddhist monks. Long after death, these ascetics continue to be revered as living Buddhas. The biographies of various monks are presented within this history of self-mummification, as is an examination of the religious beliefs involved, an amalgamation of three distinct religious traditions"--Provided by publisher